Teachers’ responses to racism and racist bullying in Dutch primary schools - Karen M. A. Sieben-Aduful; Roy A. Willems; Trijntje Völlink; Nico van der Wiel; Maria Sapouna; Pieter de Bruijn; Gemma Blok; Gemma Blok; Arjan E. R. Bos; Arjan E. R. Bos; Giel van Lankveld (Frontiers in Psychology)
BackgroundEarly in life, children with a non-White skin color, or a non-Western cultural or religious background, are susceptible of experiencing acts of racism. Since they spend a significant time of their daily life in school, teachers have a crucial role in providing a safe and bias-free environment for these children. However, teachers might find it challenging to react to bullying based on racism.AimThis study aims to investigate teachers’ experiences of and reactions to racist bullying among pupils in primary schools in The Netherlands. Additionally, this study aims to explore how racism is discussed in class.MethodWith nine semi-structured in-depth interviews teachers’ attitudes and reactions toward racist bullying were examined as well as their perceived competence and skills of handling this. In addition, teachers’ availability on tools to discuss racism in class was investigated as well. Data was analyzed using thematic analysis.ResultsThe results show that teachers emphasize a safe class climate but find it challenging addressing racist incidents, for instance determining its severity, or coping with the external influences on pupils’ racist beliefs. Most teachers also expressed to not make a distinction between racist and interpersonal bullying. While teachers expressed that they talked about racism in the classroom, it seemed that they primarily talked about cultural diversity and not racism per se.ConclusionDealing with racism and racist bullying is an important but complicated task for teachers. Providing teachers with appropriate tools to increase knowledge, awareness and skills will help them to understand the negative impact racism has on children. Further, the results implicate that a pro-active approach can stimulate teachers to critically reflect on their own racial identity, and on school methods, teaching resources and policies concerning racism.